Implications of rising energy and transportation costs for future urban development: Inner city trends in Hamburg - Alkis Henri Otto (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The focus of this study is on the consequences of rising energy costs and demographical change in the city of Hamburg. In section 2 we present a class of models that help to understand and explain patterns of urban land use. Section 3 then discusses urban land use and the population structure of Hamburg. Section 4 addresses some future economic and demographic trends and relates them to rising energy costs. Section 5 finally highlights some conclusion drawn from the analysis.
Keywords: 330